Identical Word Meaning “Interpretation and Translation” In the Context of Corpus-Based Sentences - Mega Febriani Sya; Ninuk Lustyantie; Miftahulkhairah Anwar (Universitas Djuanda, 2020)
For students whose first language is not a native English speaker, at first glance they will interpret the words